The belowground bacterial and fungal communities differed in their significance as microbial indicator of Moroccan carob habitats. (July 2020) - Khassali, Hamza; Baumel, Alex; Mahé, Frédéric; Tournier, Estelle; Tisseyre, Pierre; Prin, Yves; Ouahmane, Lahcen; Sanguin, Hervé
Highlights: Belowground microbiota is dominated by Actinobacteria, Proteobacteria and Ascomycota . Microvirgua, a potential N-fixing Rhizobiales, is predominant in carob habitats. North habitat was mainly associated with fungal pathogens. South habitat was mainly associated with stress-tolerant plant-beneficial bacteria. A core of 138 OTUs characterized the Ceratonia siliqua – Pistacia lentiscus association. Abstract: Biodiversity surveys are a pre-requisite for efficient habitat conservation policies and actions, but surveys are mainly focusing on aboveground biodiversity whereas belowground biodiversity is a key component for aboveground functioning. The current study aims at identifying the belowground microbiota associated with major plant components of carob habitats sampled in the North and South Morocco. Actinobacteria, Proteobacteria and Ascomycota were the most predominant phyla, among which only a few microbial genera dominated, i.e. Rubrobacter, Microvirga (bacteria) and Alternaria, Mortierealla and Fusarium (fungi). Microbiota structure analyses revealed a significant North/South pattern for the bacterial and fungal communities, associated with specific subsets of soil properties (C/N ratio and N-P-K, CaCO3 contents, respectively). These difference are emphasized by microbial indicator taxa analysis showing contrasted significance at the kingdom level and functionality divergences characterized by fungal pathogens in the North and stress-tolerant plant-beneficial bacteria in the South. Nevertheless, a core microbiota of 138 OTUs were revealed for the association Ceratonia - Pistacia, an indicator of Mediterranean thermophilous woodlands.